Eco-Design for Sustainability: A Mediating Role in Achieving Sustainable Manufacturing through Lean Production - Rachmawati, Christina; Mahmudy, Wayan Firdaus; Khusaini, Moh.; Kurniawan, Andi (Journal of Ecohumanism, 2025)
The increasing awareness of environmental issues and sustainability has driven the manufacturing industry to adopt a more holistic approach. Sustainable Manufacturing (SM) has emerged as a comprehensive concept that integrates environmental, social, and economic aspects into the production process. This study aims to examine the role of Eco-Design for Sustainability as a mediating factor in achieving SM through the implementation of Lean Production Practices in the Fast-Moving Consumer Goods (FMCG) industry. The research uses a quantitative approach, with data collected through questionnaires and analyzed using Structural Equation Modeling (SEM). The results show that Eco-Design for Sustainability acts as a significant mediating variable in the relationship between Lean Production Practices and SM. This implies that the implementation of Lean Production Practices, although contributing to efficiency, does not necessarily guarantee the achievement of SM without being integrated with Eco-Design. The study also found that Eco-Design, with its focus on minimizing environmental impacts throughout the product life cycle, strengthens and directs the Lean production system to be more effective in achieving SM goals. Based on these findings, the study proposes strategies to drive FMCG companies towards SM practices, including optimizing the effectiveness of Total Productive Maintenance (TPM) to improve efficiency and reduce waste, developing an Operational Excellence program, Life Cycle Optimization, digital transformation, improving employee capabilities, and developing environmentally friendly product designs. The research underscores the importance of Eco-Design for Sustainability as a key strategy in achieving SM in the FMCG industry and provides a deeper understanding of how Lean Production Practices can be effectively implemented to optimize environmentally conscious product designs.